Creating powerful brands in consumer, service and industrial markets / Leslie de Chernatony and Malcolm McDonald - 433145 De Chernatony, Leslie; McDonald, Malcolm (Oxford ; Burlington, MA : Elsevier/Butterworth-Heinemann, 2003)
36